Petits mammifères du burdigalien infèrieur (Universidade Católica, Avenida do Uruguay) - Antunes, M. Telles (2010)
Improved bromoform concentration as developped at CEPUNL allowed better recovery of small mammals'teeth. At Universidade Católica and Avenida do Uruguay 19 taxa (and a further one with doubt) were recognized. Some are new for the level and for Tagus basin: Lagopsis cadeoti and Melissiodon dominans (1st reference for the genus); Glirudinus modestus (formerly under another name); Armantomys (1st reference for this level); Peridyromys murinus (referred before under another name); Microdyromys legidensis (1st ref. of gen. and sp. for this level); and Heteroxerus rubricati, formerly reported to other species of the same genus. Both localities share the same position viz marine levels under and above. This allows us to correlate them with NS or N6 Blow's zones. Both are distinctly younger-than glauconite in underlying beds about 21 MY old (K-Ar). Small mammals point out to MN3a Neogene subunit. Fauna is much alike Lower Burdigalian ones in Spain, France, Germany and Austria. Terrestrial, maybe steppe forms predominate. Land environment was open, with scant plant cover but not devoid of trees. Peridyromys murinus numerical importance and other data suggest a not so warm climate in correspondance to a minimum temperature event. This is corroborated by associated marine fish fauna entirely without warm water stenotherm species, and by paleobotanical/palynological data. Results are in close agreement with Central Northern Spain. The localities studied here are even more interesting as direct correlations between marine and continental stratigraphical scales are possible.